Penghindaran Pajak Pada Perusahaan Sektor Aneka Industri di Indonesia Selama Masa Pandemi Covid Dari Perspektif Rasio Keuangan - Siti Nurul Khotimah; Rochmad Bayu Utomo (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Taxes for Indonesia are major source of revenue which is used for funding the government’s expenditures and development programs, while for companies as taxpayers consider that tax is a burden that will reduce net profit. Many companies attempt to pay fewer taxes because the company assumes that paying taxes means reducing the company’s economic capacity. There are several factors that affect companies in paying their taxes, such as profitability, liquidity, leverage and activity ratios. This study aims to analyze the effect of profitability ratios, liquidity, leverage and activity ratios on tax avoidance. The study method used is quantitative approach, using data from various industrial sector companies listed on Indonesia Stock Exchange during 2020 – 2021 obtained from www.idx.co.id. Based on data analysis and discussion can be concluded that profitability, liquidity, leverage and activity had no influence on tax avoidance.